2021
DOI: 10.1093/eurheartj/suab035
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure screening results from May Measurement Month 2019 in Vietnam

Abstract: Elevated blood pressure (BP) is a growing burden worldwide, leading to over 10 million deaths each year. May Measurement Month (MMM) is a global initiative to raise awareness of high BP and act as a temporary solution to the lack of screening programmes worldwide. We aimed to screen for hypertension and cardiovascular risk factors in people aged ≥18 years in the community, thereby defining the proportion of subjects with elevated BP and assess the awareness and the effectiveness of its treatment. An opportunis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
0
6
0
4
Order By: Relevance
“…Excluded patients were pregnant women and patients with psychiatric disorders. Using Cochran formula (Z = 1.96 and alpha error = 0.05) and knowing that the prevalence of hypertensive patients in Lebanon is 31.2%, 14 the minimum required sample of hypertensive patients was 330.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Excluded patients were pregnant women and patients with psychiatric disorders. Using Cochran formula (Z = 1.96 and alpha error = 0.05) and knowing that the prevalence of hypertensive patients in Lebanon is 31.2%, 14 the minimum required sample of hypertensive patients was 330.…”
Section: Methodsmentioning
confidence: 99%
“… 10 In Lebanon, in that same year, a cross-sectional study reported a higher prevalence rate of HTN (31.2%) and a poor BP control rate (28.7%) and identified that age, weight, and history of CVD were significant risk factors. 11 More recently, through the May Measurement Month (MMM) 2019 screening campaign intended to raise awareness, Najem et al recorded a rising prevalence rate of 36.6%, 12 which is higher than the rate reported by other MMM studies in Italy (31.1%) 13 and Vietnam (33.8%) 14 in the same year. Despite the high prevalence of HTN in Lebanon, there is a significant lack in the identification of symptoms and complications of this disease.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“… 10 In the next Vietnam MMM campaigns in 2018 and 2019, the proportion of hypertensive patients among surveyors was 30.3% and 33.8%, respectively, and the rate of uncontrolled BP in surveyors who taking antihypertensive medicine increased by year 46.6% and 48.8%, respectively. 11 , 12 The prevalence of important cardiovascular risk factors in Vietnam is high. Among 25–64 years old in 2015, the prevalence of hyperlipidemia was 30.2% and the prevalence of diabetes mellitus was 4.1%.…”
Section: Part I: the Diagnosis Of Arterial Hypertensionmentioning
confidence: 99%
“…Gần đây hơn, kết quả chương trình tháng 5 đo huyết áp (MMM: May Measure Month) 2017 cho thấy có 28,7% người được khảo sát mắc THA và 37,7% bệnh nhân dùng thuốc hạ huyết áp (HA) không được kiểm soát [8]. Trong các chiến dịch MMM tiếp theo của Việt Nam vào năm 2018 và 2019, tỷ lệ bệnh nhân THA trong số người khảo sát lần lượt là 30,3% và 33,8%, và tỷ lệ không kiểm soát được huyết áp ở người có điều trị tăng tương ứng 46,6% và 48,8% [9], [10]. Dự báo trong những năm tới số người mắc bệnh tăng huyết áp sẽ còn tăng do các yếu tố liên quan như: hút thuốc lá, lạm dụng rượu bia, thừa cân-béo phì, ít vận động, … đang ngày càng phổ biến.…”
Section: đặT Vấn đềunclassified